Phenotype Characteristics of Alabio Ducks (Anas Platyrhynchos Borneo) in South Kalimantan - Herliani Herliani; Abrani Sulaiman; Adnan Yasser (Journal of Wetlands Environmental Management, 2022)
Research on the phenotype characteristics of Alabio Ducks (Anas Platyrhynchos Borneo) in South Kalimantan was conducted to determine the phenotypic characteristics of 3 central Â Alabio ducks (Hulu Sungai Utara, Banjar and Tabalong Regencies). The materials used in this study were 480 Alabio ducks, aged Â± 6 months, consisting of 30 males and 450 females. The method used in this research was a survey method that was multistage random sampling. The variables observed were dominancy and pattern colors of feathers on neck, breast, back, wing, leg, and tail, beak color and shank color. Based on the results of observations in the Tabalong, HSU and Banjar Regencies, the results show that Alabio ducks have 6 kinds of colors that appear on observed body parts, namely black, grayish-white, blackish-gray, brownish-gray, brown, brownish-white, black, and brownish-white, light-brown spots or dark brown spots on breast feather. The colors of the beak and shank of male and female Alabio ducks are light-yellow or whitish yellow. While the uniform color characteristics are found in male and female Alabio ducks, namely on the grayish-white neck feathers, blackish gray and bluish green on wing feathers, blackish and brownish gray on back-feathers, brownish and black gray on tail-feathers and brownish-white, light brown spots. or dark brown spots on breast-feather. In conclusion, there are not many differences in both the dominant feather color, the variation in the color of the feathers, the beak, the shank of the Alabio ducks, since most of them come from the similar ancestors.